The influence of knowledge sharing motives on the well-being of academic staff - Abdul Kadir, Hasnah; Wok, Saodah; Ruslan, Norbaiduri (2021)
The well-being of academic staff is important towards their work performance, deliverables, and efficiency for success and sustainability of higher learning institutions. Acknowledging the importance of well-being, this study examined the influence of knowledge-sharing motives on the well-being of academic staff. Knowledge sharing motives comprised of enjoyment, intrinsic rewards, and collegiality induced by communication devices and platforms were the focus of this study. In specific, the objectives of the study were to find the (1) level of well-being and knowledge-sharing motives; (2) correlation between well-being and knowledge-sharing motives; and (3) best predictor of well-being. The under-pinning theoretical framework employed was The PERMA model by Seligman (2011) that measured well-being using five dimensions: Positive emotion, engagement, relationships, meaning of life, and accomplishment. This study however, replicated the model with some amendments, with the addition of spirituality and the exclusion of meaning of life, to accommodate the Islamic philosophy that permeates the establishment of the International Islamic University Malaysia (IIUM), where the study was conducted, thus, the PERMA model was changed to PERSA. This study employed a quantitative research design by using survey method. Self-administered questionnaires were used to solicit information from the respondents by using stratified random sampling. A total of 333 academic staff participated in the study. The findings showed that the levels of well-being and knowledge-sharing motives were high, and they correlated significantly. The best predictor of well-being was the intrinsic rewards of the knowledge-sharing motives. Therefore, the findings of the study supported the PERSA model.